Thermochemical production of ammonia using sunlight, air, water and biomass - Michalsky, Ronald (Kansas State University, 2012)
Approximately 45% of the global hydrogen production (from fossil fuels such as natural gas or coal totaling 2% of the global energy generation) is absorbed as feedstock in the synthesis of over 130 million metric tons ammonia (NH[subscript]3) annually. To achieve food security for a growing world population and to allow for additional uses of the nitrogen-fertilizer for production of bio-energy feedstock or as combustion fuel or H[subscript]2 carrier - demand for NH[subscript]3 is projected to increase. This work pursues the synthesis of ammonia at atmospheric pressure and without fossil fuel. Conceptually, concentrated solar radiation is utilized to transfer electrons from the lattice oxygen of a transition metal oxide to the metal ion. This yields a metallic reactant that provides the reducing power for the subsequent six-electron reductive cleavage of N[subscript]2 forming a transition metal nitride. In a second reaction, the generated lattice nitrogen is hydrogenated with hydrogen from H[subscript]2O to NH[subscript]3. This furnishes the transition metal oxide for perpetuated NH[subscript]3 synthesis. Theory and experimentation identified manganese nitride as a promising reactant with fast diffusion characteristics (8 ± 4 x 10[superscript]-9 cm[superscript]2 s [superscript]-1 apparent nitrogen diffusion constant at 750 degree C) and efficient liberation of 89 ± 1 mol% nitrogen via hydrolysis at 500 degree C. Opposed to only 2.9 ± 0.2 mol% NH[subscript]3 from manganese nitride, 60 ± 8 mol% of the nitrogen liberated from molybdenum nitride could be recovered as NH[subscript]3. Process simulation of a Mo-based NH[subscript]3 synthesis at 500-1200 degree C estimates economically attractive production under fairly conservative process and market conditions. To aid the prospective design of a Mn or Mo-based reactant, correlating the diffusion constants for the hydrolysis of seven nitrides with the average lattice nitrogen charge (9.96-68.83%, relative to an ideal ionic solid) indicates the utility of first-principle calculations for developing an atomic-scale understanding of the reaction mechanism in the future.
Keywords: Ammonia; Fertilizer; Fuel; Solar thermochemical reaction cycle; Economcis; Reaction mechanism; Chemical Engineering (0542)